1992
DOI: 10.1083/jcb.117.6.1223
|View full text |Cite
|
Sign up to set email alerts
|

Actin-facilitated assembly of smooth muscle myosin induces formation of actomyosin fibrils

Abstract: Abstract. To identify regulatory mechanisms potentially involved in formation of actomyosin structures in smooth muscle cells, the influence of F-actin on smooth muscle myosin assembly was examined. In physiologically relevant buffers, AMPPNP binding to myosin caused transition to the soluble 10S myosin conformation due to trapping of nucleotide at the active sites. The resulting 10S myosin-AMPPNP complex was highly stable and thick filament assembly was suppressed. However, upon addition to F-actin, myosin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…Under the activated condition, phosphorylation of caldesmon abolishes its own affinity for myosin (56). As discussed above, binding of myosin monomers to thin filaments could also provide guidance for thick filament formation (1,39).…”
Section: Possible Mechanisms For Thick Filament Assembly In Intact Smmentioning
confidence: 99%
“…Under the activated condition, phosphorylation of caldesmon abolishes its own affinity for myosin (56). As discussed above, binding of myosin monomers to thin filaments could also provide guidance for thick filament formation (1,39).…”
Section: Possible Mechanisms For Thick Filament Assembly In Intact Smmentioning
confidence: 99%
“…Importantly, myosin filament length is not fixed (26), but rather is dynamically determined, changing even during the course of a single contraction (27,28). In addition, myosin filament length appears to be influenced by recent muscle length history (e.g., length oscillation of relaxed ASM shortens myosin filaments) (29), by the length of actin filaments which seem to provide a template for myosin polymerization (30)(31)(32), and by the phosphorylation state of the 20-kD regulatory myosin light chain (MLC 20 ) (33)(34)(35)(36)(37)(38). We exploited the latter to obtain indirect evidence suggesting that myosin filament length modulates FFIR.…”
Section: Modulation Of Myosin Filament Lengthmentioning
confidence: 99%
“…Phosphorylation of MRLC leads to bipolar myosin filaments, resulting in the formation of acto-myosin fibers (Applegate and Pardee, 1992). It has been reported that MRLC is phosphorylated at the cleavage furrow (Matsumura et al, 1998;Murata-Hori et al, 1998;Ueda et al, 2002).…”
Section: Rho Activity Is Required For Accumulation Of Myosin II At Thmentioning
confidence: 99%